Growth and yield of okra influenced by different types of fertilizers and netting - Muqtadir, MA; Islam, MA; Haque, T; Nahar, A (Progressive Agriculture, 2019)
An experiment was conducted at the Horticulture Farm of Bangladesh Agricultural University, Mymensingh during the period from March 2017 to June 2017 with a view to evaluate the effect of different types of fertilizer and netting on the growth and yield of okra. The experiment consisted of 4 levels of fertilizer following cow dung 15 t/ha (F1), inorganic fertilizer (NPK) (F2), combined application of cow dung (2/3) + inorganic fertilizer (1/3) (F3), control (F4) and 2 levels of mosquito netting (N0 = control with no netting, N1=blue colour Netting). The experiment was laid out in Randomized Complete Block Design (RCBD) with 3 replications. Overall, the growth like plant height, leaf length, pod length, pod diameter and pods numbers of okra was found higher from the combined effect of F3N1 which was significantly different from other treatments combination. The lowest growth and yield of okra was found from the treatment combination of F4N0 (control). First flowering were observed in F3N1 at 39 days after planting of okra seeds. The control treatment without net gave the lowest production of okra compared to combination of inorganic fertilizer and cow dung with netting. In case of fertilizers effect, the highest yield (16.06 t/ha) was found from F3. Blue colour net gave the highest yield (10.99 t/ha) compared to without net (8.88 t/ha). The highest yield of okra (17.55 t/ha) was found from the combined effect of F3N1 which was 78.52% higher compared to control treatment combination F4N0 (3.77 t/ha). Progressive Agriculture, Vol. 30, Suppl. 1: 1-9, 2019